Laparoscopic hydrocelectomy of the canal of Nuck in adult female: Case report and literature review. (2020) - Shahid, Fakhar; El Ansari, Walid; Ben-Gashir, Mohamed; Abdelaal, Abdelrahman
Highlights: A very rare case of hydrocele of canal of Nuck in elderly lady. This case expands the clinical and intraoperative potential differential diagnosis of adult female groin masses. Hydrocele of canal of Nuck must be considered one of the differential diagnosis in ladies with inguinal masses. Laparoscopic TAPP is superior to open approach in managing such cases. Probably the first case of hydrocele of canal of Nuck in adult female operated laparoscopically in the Middle East and North Africa (MENA) Region, and the fourth such case worldwide. Abstract: Introduction: Among adult females, Hydrocele of Canal of Nuck (HCN) is a very rare condition. The majority of the reported cases of HCN were not conclusively diagnosed until surgery was performed on a suspected inguinal hernia. To the best of our knowledge, this is the first case of laparoscopically operated HCN in adult female in Middle East and North Africa Region, and the fourth such case worldwide. Presentation of case: A 36-year-old female presented with a painful small swelling in the right groin of 3 months duration. The swelling extended to the right labia majora while standing, and disappeared when the patient was in prone position. There was no lymph node enlargement, no other masses in the abdomen, and no swelling in the contralateral side. Ultrasonography was undertaken and the patient was admitted electively for laparoscopic exploration and repair of non-complicated right inguinal hernia. She was known to have dyslipidemia on medications. Further history and physical examination were unremarkable. Intraoperatively it was diagnosed to be right-sided HCN which was excised and repaired by mesh fixation using transabdominal preperitoneal (TAPP) approach. Her follow up course was unremarkable. Conclusions: This case expands the clinical and intraoperative potential differential diagnosis of adult female groin masses. Surgeons should consider such cases when they observe such swellings intraoperatively. Laparoscopic TAPP approach in such cases is a superior diagnostic and treatment modality.